2012
DOI: 10.1007/s10903-012-9665-8
|View full text |Cite
|
Sign up to set email alerts
|

Immigrating to the US: What Brazilian, Latin American and Haitian Women Have to Say About Changes to Their Lifestyle That May be Associated with Obesity

Abstract: Our goal was to explore the perceived determinants of obesity in Brazilian, Latin American and Haitian women. This is part of an ongoing community-based participatory intervention. Focus groups by immigrant group were conducted and themes extracted. Women expressed differences in beliefs, attitudes, and barriers regarding diet and physical activity in the US versus their home country. Participants thought food in the US is “less natural,” there is less time for preparation, and there is more variety. The weath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 42 publications
4
45
0
Order By: Relevance
“…Members of younger and bigger households are also more likely to choose convenience food, while older households are more likely to maintain traditional meals 66 . Immigrants report that acculturation is often associated with an increase in stress 69,70,71 and stress and stress-related disorders may play an important role in the development of obesity 67,68 .…”
Section: Sub-saharan Africansmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of younger and bigger households are also more likely to choose convenience food, while older households are more likely to maintain traditional meals 66 . Immigrants report that acculturation is often associated with an increase in stress 69,70,71 and stress and stress-related disorders may play an important role in the development of obesity 67,68 .…”
Section: Sub-saharan Africansmentioning
confidence: 99%
“…Some studies showed an increase in fat and sugar intake and a decrease in fruit and vegetable consumption after immigration 77 , while others observed a decrease in vegetarianism and an increase in the consumption of caffeinated beverages 24 . Food availability and prices are determinants of food choices among immigrants 70 , while the factors age and generation are two major determinants of the extent of dietary change 5 .…”
Section: Sub-saharan Africansmentioning
confidence: 99%
“…These were consistent with findings from Hughes et al (.85 for demandingness and .82 for responsiveness). 9 Compared with other populations, Whites, African Americans, Hispanics, and Latin Americans (Table 5 9- 12,19 ), mothers in this study showed high demandingness (3.53) and somewhat lower responsiveness (1.08). Correlations for the FNPA were .80, which were higher than Ihmels's findings (alpha=.72).…”
Section: Discussionmentioning
confidence: 48%
“…Dietary acculturation is multi-factorial in that diverse factors affect what foods someone will accept and reject, and how quickly they will acculturate. Some of these factors include accessibility (including cost and availability), education level and income (Hassan & Hekmat, 2012;Tovar et al, 2012;Chen, 2010).…”
Section: Acculturation and Dietmentioning
confidence: 99%
“…Often the immigrant tries to choose traditional foods, but if those foods are not available, they substitute with the host's foods (Hassan & Hekmat, 2012;Tovar et al, 2012). One study conducted on Chinese immigrants in the U.S. showed that the strongest predictor of dietary acculturation was the cost of food as well as the availability of healthy foods (Chen, 2010).…”
Section: Acculturation and Dietmentioning
confidence: 99%